Matters of life and death: locating the end of life in lifespan-oriented hci research - Massimi, Michael; Odom, William; Banks, Richard; Kirk, David (CHI 2011 - Annual Conference on Human factors in Computing Systems, 2011)
Examining developmental periods of the human lifespan has been a useful tradition for focusing HCI research (e.g., technologies for children or the elderly). In this paper, we identify the end of life as another period of the human lifespan that merits consideration by technology designers and researchers. This paper maps out current and future research in HCI at the end of life by first describing how this area raises questions concerning materiality and artifacts, social identities, temporality and methodologies. Having provided a description of the richness of this area, we then frame it against HCI traditions and practices in an orientation we term the lifespan-oriented approach. This paper maps early efforts in end of life research, structures and suggests areas for continued work, and situates the end of life among existing areas of HCI research.